PERAN MEDIASI JEJARING USAHA DALAM HUBUNGAN LITERASI DIGITAL DAN ORIENTASI PASAR TERHADAP KINERJA UMKM DI ERA EKONOMI DIGITAL - Raudatul Jannah; Muh. Fahrurrozi; Farhana Muhammad (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2026)
The study was conducted in Selong City, East Lombok Regency, involving This study analyzes the effects of digital literacy and market orientation on MSME performance, with business networks positioned as an intervening variabel. The study responds to the limited empirical explanation of how MSME internal capabilities are converted into measurable performance through networking mechanisms, particularly in small-city business ecosystems. An explanatory quantitative survey was conducted involving 226 MSME actors in Selong City, East Lombok Regency, selected using purposive sampling. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS. The results show that the model struktural has moderate explanatory power (R² = 0.455) and adequate predictive relevance (Q² = 0.379). The study contributes to the Resource-Based View and Social Capital Theory by demonstrating that business networks function as a strategic mediating mechanism that converts digital capability and market orientation into stronger MSME performance in the digital economy.